Supporting Capacity Building in Health Service Provision in Eritrea via Distance Learning Master’s Programmes: The Challenges and Rewards - Corlett, Joanne; Martindale, Linda (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
A qualitative study investigating the experiences and effects on practice of Eritrean healthcare professionals studying for a postgraduate degree by distance learning is reported. The programme is delivered via online learning together with in-country teaching visits. Two focus group discussions with 19 postgraduate students were conducted. Online learning is challenging due to intermittent connectivity and power cuts, but students have developed their own solutions to overcoming these difficulties. Thematic analysis generated four themes. Students who are embedded within the Eritrean context are experiencing a process of self-development, both academic and personal. This self-growth is facilitating the development of resilience and confidence building, enabling students to have a positive influence on health service provision, thus impacting on the Eritrean context. Students are developing life-long skills that will support the continuing development of healthcare systems in Eritrea long after they have completed their distance learning programme.